Lumbar Spondylolysis in Juveniles from the Same Family: A Report of Three Cases and a Review of the Literature - Atsuhisa Yamada; Koichi Sairyo; Isao Shibuya; Ko Kato; Akira Dezawa; Toshinori Sakai (Case Reports in Orthopedics)
Spondylolysis is reported as a stress fracture of the pars interarticularis with a strong hereditary basis. Three cases of lumbar spondylolysis in juveniles from the same family are reported, and the genetics of the condition are reviewed. The first boy, a 13-year-old soccer player, was diagnosed with terminal stage L5 bilateral spondylolysis with grade 1 slippage. The second boy, a 10-year-old baseball player, had terminal stage right side unilateral spondylolysis. The third boy, also a 10-year-old baseball player, was diagnosed with early stage bilateral L5 spondylolysis. The second and third boys are identical twins, and all three cases exhibited concomitant spina bifida occulta. Lumbar spondylolysis has a strong hereditary basis and is reported to be an autosomal dominant condition.